Six days, seven nights - Reitman, Ivan.; Ford, Harrison, 1942-; Heche, Anne.; Schwimmer, David, 1966-; Morrison, Temuera; Obradors, Jacqueline; Edelman, Randy; Browning, Michael; Caravan Pictures; Northern Lights Entertainment (Firm); Touchstone Home Video (Firm) (Burbank, Calif. : Touchstone Home Video, 1998)
A dream vacation turns into a hilarious tropical nightmare when a rough-hewn cargo pilot takes a sharp-tongued yuppie on a quick flight to Tahiti, only to crash in a storm, stranding the two on a deserted island.
Originally released as a motion picture.
Special features: Theatrical trailer ; Additional titles.
Director of photography, Michael Chapman ; music by Randy Edelman ; edited by Sheldon Kahn ; assistant director, Michael Neumann.
Harrison Ford, Anne Heche, David Schwimmer, Jacqueline Obradors, Temuera Morrison, Allison Janney, Douglas Weston, Cliff Curtis, Danny Trejo.
Rated PG-13.
DVD, Dolby digital, region 1, NTSC, widescreen (2.35:1) presentation.
Keywords: Vacations -- Drama; Survival -- Drama; Man-woman relationships -- Drama; Closed caption video recordings; DVD-Video discs; Adventure films; Action and adventure films; Drama; Feature films; Video recordings for the hearing impaired